NKX2-1 gene is targeted by H19 lncRNA and is found to be overexpressed in benign nodular goiter tissues - Seyed-Morteza Javadirad (Brazilian Journal of Otorhinolaryngology, 2024)
Objective: Nodular goiter may increase the risk of thyroid cancer, but the genetic factors contributing to nodular goiter are not well understood. There is an overexpression of H19 lncRNA in goiter tissue and its target remains unknown. In this study, we attempted to identify a new target for H19 in the context of goiter development. Methods: Using interaction energy calculations, the interaction between NKX2-1 mRNA and H19 lncRNA was examined. Putative microRNAs were found at the H19 lncRNA target site with the highest affinity for NKX2-1. RNAseq data was analyzed to determine the tissue specificity of gene expression. Samples were taken from 18 goiter and 18 normal tissues during thyroidectomy. The expression of NKX2-1 was determined by RT-qPCR using specific primers. Results: The interaction between NKX2-1 and H19 was characterized by six local base-pairing connections, with a maximum energy of −20.56 kcal/moL. Specifically, the sequence that displayed the highest affinity for binding with H19 overlapped with the binding site of has-miR-1827 to NKX2-1. It was found that NKX2-1 is exclusively co-expressed with H19 in normal thyroid tissue. As compared to adjacent normal tissues, nodular goiter tissues have a significant overexpression of NKX2-1 (relative expression = 1.195, p =  0.038). Conclusion: NKX2-1 has been identified as the putative target of H19 lncRNA, which is overexpressed in nodular goiter tissues significantly. Level of Evidence: 4.